Nuclear heating measurements by gamma and neutron thermometers - Van Nieuwenhove R.; Vermeeren L. (EPJ Web of Conferences, 2020)
A gamma thermometer suitable for very high gamma heating levels (up to 20 W/g) has been designed and modelled by means of detailed finite element calculations. Based on a sensitivity analysis, the predicted accuracy of this gamma thermometer is better than 5 %. A novel miniaturized gamma thermometer is proposed in which a single thermocouple is used as the gamma absorption element, allowing a reduction of the sensor diameter down to 3 mm. Monte Carlo calculations (by MCNP) have been performed to assess the relative contribution of neutrons to the nuclear heating in a gamma thermometer. Calculations have been performed for gamma thermometers with an inner body made of various materials, such as stainless steel, tungsten, molybdenum and rhodium. By using gamma thermometers made of different materials, it will be possible to deduce the nuclear heating rates in these materials and also to separate out the neutron and gamma heating contributions. The Monte Carlo calculations show that nuclear heating of rhodium is mainly due to neutrons, converting the rhodium gamma thermometer effectively in a neutron thermometer. The sensitivities of the gamma thermometers with W, Mo or Rh as heated materials have been modelled by finite element calculations. It is found that both the Mo and the Rh based sensor have a very linear response up to a nuclear heating of 20 W/g.